Silver-doped titanium dioxide nanotubes for photoelectrocatalytic degradation of acid orange 52 - Lopez, Edgar Clyde R.; Perez, Jem Valerie D.; Ocon, Joey D. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Advanced oxidation processes (AOPs) such as photocatalysis and electrocatalysis has been used in the past to degrade recalcitrant organic pollutants in wastewater using semiconductor metal oxides. In particular, azo dyes have been widely studied because of its difficulty to be treated using conventional water treatment methods. Titanium dioxide is the most used photocatalyst because of its low cost, wide availability, and non-toxicity. However, it requires UV light for photoactivation due to its fast electron-hole recombination and wide band gap. Doping TIO₂ with transition metals such as silver is one way to extend its photoactivity in the visible light region. However, most studies focused on doping TIO₂ nanoparticles which neccessitate further separation after use. Furthermore, previous studies have been conducted on Ag-doping but most used expensive synthesis approaches. In this study, highly-ordered Ag-doped TIO₂ nanotubes (Ag-TiNTs) were synthesized by double anodization of Ti sheets. Doping was achieved using AgNO₃ in anodization electrolyte as Ag precursor. The as-anodized TiNTs were calcined, caharacterized, and used as photoelectrodes for degradation of Acid Orange 52 (AO 52). The effects of light intensity and electrical bias on the degradation of AO 52 were investigated. The study showed that Ag was homogeneously doped on pristine TiNTs. Kinetic studies under UV and visible light illumination showed the superiority of photoelectrocatalysis over photocatalysis and electrocatalysis alone. Increasing the applied potential and light intensity both resulted in faster degradation of AO 52. Doping with Ag was shown to enhance the catalytic activity of pristine TiNTs in UV and visible light. Ag acts as an electron trap that minimizes electron-hole recombination causing a higher lifetime for electron-holes to generate free radicals. Overall, Ag-doping was shown to enhance the photoelectrocatalytic performance of pristine TiNTs in degrading AO 52 under UV and visible light illumination.
Thesis (Master of Science in Chemical Engineering)--University of the Philippines Diliman
Keywords: Photocatalysis; Electrocatalysis; Titanium dioxide nanotubes; Doping; Anodization; Acid orange 52.